Urban Society In Roman Italy - Cornell, Tim J.; Lomas, Kathryn (Taylor & Francis, 1995)
This collection of original essays focuses upon Roman Italy where, with over 400 cities, urbanization was at the very centre of Italian civilization. Informed by an awareness of the social and anthropological issues of recent research, these contributions explore not only questions of urban origins, interaction with the countryside and economic function, but also the social use of space within the city and the nature of the development process.; These studies are aimed not only at ancient historians and classical archaeologists, but are directed towards those working in the related fields of urban studies in the Mediterranean world and elsewhere and upon the general theory of towns and complex societies.